Inaccurate haemoglobin estimation in Waldenström's macroglobulinaemia: unusual reaction with monomeric IgM paraprotein. Issue 12 (December 1993) - Goodrick, M J; Boon, R J; Bishop, R J; Copplestone, J A; Prentice, A G
Abstract : Automated blood counts from a patient with Waldenström's macroglobulinaemia repeatedly failed critical limit standards set for mean cell haemoglobin concentration and mean cell haemoglobin. Haemoglobin estimation was higher than that suggested by clinical examination, symptoms, and the spun haematocrit. This was found to be due to an interaction between the Coulter lysing agent and monomeric IgM paraprotein in the patient's plasma, creating a precipitate which was optically dense at 525 nm.